Genetic correlations between longevity and conformation traits in the Czech Holstein population - Zavadilová, L.; Štípková, M. (Czech Journal of Animal Science, 2012)
Genetic correlations between longevity and conformation traits were estimated using data on Czech Holstein cows first calved in the years 1993-2008. Longevity traits considered were length of productive life and number of lactations initiated and their functional equivalents (i.e. the longevity traits corrected for milk production). Conformation traits were twenty one linear descriptive type traits, six composite traits and height at sacrum measured in cm. A possible nonlinear relationship between conformation and longevity traits was also investigated. The heritabilities ranged from 0.05 to 0.43 for conformation traits and from 0.03 to 0.05 for longevity traits. Low to moderate genetic relationships between conformation and longevity traits were found. The genetic correlations were higher for functional longevity than for direct longevity traits. Negative genetic correlations with all longevity traits were found for height at the sacrum, stature, dairy form, body conformation, and capacity. Final score showed weak genetic correlation with all analyzed longevity traits. Positive genetic correlations occurred between feet and legs and direct longevity and functional longevity (0.19, 0.14) and between udder and direct longevity (0.10). Body condition score and angularity showed strong genetic correlations with functional longevity (body condition score 0.30, angularity -0.31). Foot and leg traits showed weak genetic correlations with longevity traits except rear legs set (side view) (-0.24) and hock quality (0.19). The udder traits showed inconsistent and rather weak genetic correlations with longevity traits, with the exception of a stronger genetic correlation between rear udder width and functional longevity (-0.22) and between central ligament and number of lactations (-0.18, -0.19). The teat traits showed always negative genetic correlations with longevity traits. The strongest correlations were found for rear teat position (-0.28) and the weakest for teat length (-0.03). Some conformation traits showed markedly stronger genetic correlations with functional longevity than with direct longevity (rear udder width and rear udder height, dairy form, body condition score, angularity, rear legs set (side view), rear legs rear view). A quadratic relationship between conformation and longevity traits did exist. Even if the linear relationship generally prevailed, the quadratic relationship should be taken into account.
Keywords: cows; Holstein breed; longevity; conformation traits; genetic correlation; nonlinearity